First German experience using augmented reality for neuroanatomy education in undergraduate medical students: a feasibility and questionnaire-based study - Zhao, Yining; Bozhkov, Yavor; Chen, Xiaolei; Fuchs, Katharina; Buchfelder, Michael; Fester, Lars; de Oliveira, Daniela Souza; Del Vecchio, Alessandro; Kinfe, Thomas M. (Educational technology research and development, 2024)
To date, neuroanatomy education courses are still based on two-dimensional (2D) illustrations combined with cadaver dissections. To gain a more comprehensive understanding of neuroanatomy, we offered mixed reality experience using a head-mounted device (HMD) for medical students during their neuroanatomy course. This pilot study´s purpose was to determine whether or not, from a pragmatic view, the utilization of 3D VR/AR via HMD is viable in neuroanatomy courses and aimed to evaluate the feasibility of using mixed reality in neuroanatomy education and experiences with the mixed reality brain environment. A virtual model including major neuroanatomical structures was generated from a MRI dataset using computer software. Major structures were displayed and annotated in different combinations and scenes using an HMD. Along with the 3D virtual model, the original MRI was presented in a virtual form inside the HMD. Conventional 2D anatomical atlases were also used during the seminar. Thirty medical students (11 male; 19 female; average: 23.2 years) in their second year were recruited from October 2022 to February 2023 for this study via open invitation during neuroanatomy lectures. Participants were asked to wear the HMDs and to take a 2 h neurosurgery-oriented mixed reality seminar given by a neurosurgical teacher in small groups (3 per group). A questionnaire comprising five levels of options was designed and used to evaluate the feasibility/effectiveness of this seminar. The mixed reality environment, comprising virtual 3D models of major brain structures, virtual MRI, and conventional 2D anatomical graphs, was uncomplicated and feasible for neuroanatomy education of the medical students. According to our survey, all participants (30/30) strongly agreed that the 3D visualization of the spatial relationships between anatomical structures was easy to use as a meaningful supplement. Twenty-one of the participants strongly agreed and nine quite agreed that they had more interest in neuroanatomy. Eighty-seven percent of the participants were strongly satisfied with the mixed reality seminar versus conventional neuroanatomy seminars, and the other 13% were quite satisfied with the mixed reality approach. Most of the participants (20/30) strongly agreed that mixed reality helped them memorize the anatomical structures, and 9/30 participants quite agreed. Seventy-four percent of the participants agreed that immersive mixed reality is better than 3D models presented in 2D devices. Over half of the participants could wear the HMD for over 60 min (65%) without any ophthalmic discomfort, and the HMD was reported to be well tolerable (57%). Nearly three-fourths of the participants found that handling the device was extremely simple, and the other part indicated that it was quite simple. No health issues or discomfort on the forehead occurred. As a consequence, the seminar has been officially classified as an elective neuroanatomy course for second-year medical students. The use of mixed reality with HMDs to illustrate 3D brain models relevant for the neuroanatomy cadaver dissection education and described in our study was positively perceived by the medical students and demonstrated the viability of 3D AR/VR via HMD in neuroanatomy education. Future research lines are warranted to determine the usefulness of mixed reality technologies to effectively support medical students education of the complex three-dimensional brain anatomy.
Online veröffentlicht: 16. Dezember 2024
Gesehen am 21.03.2025